2022
DOI: 10.52633/jemi.v4i1.153
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Endogenous Culture, Local Resources, Eco-Friendly Environment and Modern Strategy Development on Entrepreneurial Development

Abstract: Entrepreneurship is currently a global concern as its great contribution and key solutions to the economy by providing more job opportunity, income generation area, the basis for technology transfer and development and non-economic with regard to sustaining political and social activities, increasing intention of equal resource sharing and active participation in economic development is gradually increasing. This significant contribution became challenged with many key determinant factors such as indigenous cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The rate of worker turnover is increasing as a result of ineffective leadership (Karunakaran & Temam, 2022;Gobena & Kant, 2022;. One problem affecting commercial businesses is the dearth of transformative leaders as a result of poor management (Kant & Tufa, 2022;Alade, 2022).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The rate of worker turnover is increasing as a result of ineffective leadership (Karunakaran & Temam, 2022;Gobena & Kant, 2022;. One problem affecting commercial businesses is the dearth of transformative leaders as a result of poor management (Kant & Tufa, 2022;Alade, 2022).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The SMEs in Ethiopia have poor levels of innovation in the small and micro-enterprise sectors, according to the studies listed below. For instance, the research by Talegeta (2014) and Gobena & Kant (2022) showed that there are several impediments to innovation, such as a shortage of trained workers, insufficient R&D, business size, and excessive expenses of innovation spending. In a similar vein, (Kassa & Getnet Mirete, 2022) found that government backing, access to infrastructure, owner leadership, entrepreneurial training, and entrepreneurial mentality all had an impact on the creativity of micro and small businesses engaged in service and manufacturing.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…As urbanization accelerates and technology becomes more accessible, a wave of creativity and innovation is reshaping the contours of business across the continent. Studying entrepreneurship in Africa is of paramount significance in the global economic landscape (Gobena and Kant, 2022.). The continent's diverse markets, untapped potential, and the resilience of its entrepreneurs present unique opportunities and challenges that merit thorough examination (Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%